PENGARUH PEMILU.AI SEBAGAI PLATFORM DATA POLITIK DIGITAL BERBASIS AI DAN BIG DATA TERHADAP KESUKSESAN KAMPANYE POLITIK DI INDONESIA - Rafif, Faiz Akmal; Marsheila, Fitri; Rushufah, Rana Rau’atur (Journal of Social Contemplativa, 2024)
The use of AI has now experienced significant developments compared to previous times, especially in the current digital era. Pemilu.AI is present as a digital political platform that offers political data from various electoral districts in order for legislative candidates to develop smart, innovative and efficient political campaign strategies. The findings in this article explain that the data held by the Pemilu.AI platform can help legislative candidates understand crucial sectors in an electoral district, such as vote acquisition data in the 2019 legislative election (Pileg) which is useful for understanding political preferences and identifying political trends, online media data can be used to find trends and topics that are being discussed on social media and online news which can be integrated with legislative candidates' campaigns, etc. This article will examine in more depth what features in the form of data the Pemilu.AI platform has and how these data features supported by AI and Big Data can help legislative candidates achieve success in political campaigns and competitions in Indonesia.